Musicus danicus eller Danske sangmester - Schacht, Matthias Henriksen 1660-1700; Skjerne, Godtfred (Kopenhagen H. Hagerup, 1928)
Bibliotheca musica, sive Authorum musicorum catalogus.--Phonologia, om Siunge-konsten.--Tonologia, om Dee musicaliske intonationer.--Melothesia, om Compositionen.--Tastologia, huorledis mand skal spille een general bass, effter noderne paa eet claveer.
Published with support from the Carlsberg Foundation. Printed in a circulation of 250 copies.
The manuscript (previously unpublished) of this work is in the Royal library, Copenhagen (Ny kgl. saml. 109k. Fol.) The preface is dated 1687.
Keywords: Denmark; Music theory